2022
DOI: 10.3390/brainsci12030301
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive Attentiveness Induces Significantly More PFC Activation during a Synchronized Linguistic Task Compared to a Motor Task as Revealed by Functional Near-Infrared Spectroscopy

Abstract: Currently, there is little understanding of how interoceptive attentiveness (IA) affects brain responses during synchronized cognitive or motor tasks. This pilot study explored the effect of explicit IA manipulation on hemodynamic correlates of simple cognitive tasks implying linguistic or motor synchronization. Eighteen healthy participants completed two linguistic and motor synchronization tasks during explicit IA and control conditions while oxygenated (O2Hb) and deoxygenated (HHb) hemoglobin variations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 64 publications
1
24
0
Order By: Relevance
“…In the second fNIRS study, hemispheric lateralization was reported with an increase in O2Hb in the right PFC when intentional attention toward breathing was induced during a cognitive synchronization task, namely a linguistic task [12]. According to previous studies, the right PFC appears to support the execution of IA tasks [6,23,24] and sustained and goal-directed attention [18].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the second fNIRS study, hemispheric lateralization was reported with an increase in O2Hb in the right PFC when intentional attention toward breathing was induced during a cognitive synchronization task, namely a linguistic task [12]. According to previous studies, the right PFC appears to support the execution of IA tasks [6,23,24] and sustained and goal-directed attention [18].…”
Section: Introductionmentioning
confidence: 89%
“…Previously, single-brain studies were carried out to investigate the neural correlates of IA manipulation (operationalized as focused on breathing) on the inter-personal synchronization necessary for performing joint tasks [12][13][14][15]. In two recent studies, functional near-infrared spectroscopy (fNIRS) was used to record the oxygenated hemoglobin (O2Hb) changes during joint tasks involving motor and cognitive synchronization, while the participants were required to concentrate on their breathing to better understand the hemodynamic correlates of IA manipulation in interpersonal synchronization [12,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the participants had to synchronize their finger movements with the experimenter sitting in front of them. The total duration of the task was of 3 mins (for the full description of the tasks; see Balconi and Angioletti, 2022).…”
Section: Procedural Stepsmentioning
confidence: 99%
“…It is interesting to note that this evidence was significantly observed for the cognitive (i.e., linguistic) task, and not for the motor task. If taking into account the direct correlation between interoceptive correlates (and the focus placed on controlling them) and motor performance, as well as the neuroanatomic closeness between the interoceptive and the motor region, this finding appeared paradoxical (Balconi and Angioletti, 2022). Furthermore, this pilot study considered a limited sample size, and the functional near-infrared spectroscopy (fNIRS) technique was not applied to the somatosensory cortical regions or the rest of the brain, but simply over the PFC (Balconi and Molteni, 2016).…”
Section: Introductionmentioning
confidence: 99%